Tindak Tutur Perlokusi Pidato Joko Widodo dalam Unggahan Instagram tentang Peresmian Persemaian Mentawir, Penajam Paser Utara, Kalimantan Timur - Brenada Anggelika Refita Lasytiara; Marista Dwi Rahmayantis; Nur Lailiyah (TSAQOFAH, 2026)
Political speeches not only function to convey information but also produce certain effects on listeners’ thoughts, attitudes, emotions, and actions through perlocutionary speech acts. This study aimed to describe the forms and functions of perlocutionary speech acts in President Joko Widodo’s speech on the Inauguration of the Mentawir Nursery in Penajam Paser Utara, Kalimantan, which was uploaded through the official Instagram account @jokowi. The study employed a pragmatic approach with a qualitative descriptive design. The research data consisted of utterances containing perlocutionary speech acts in the speech video. Data were collected using the observational method with a note-taking technique and were subsequently analyzed based on the Miles and Huberman model through the stages of data reduction, data display, and conclusion drawing. Data validity was examined through theoretical triangulation. The results showed that the forms of perlocutionary speech acts comprised persuading in 7 instances, raising awareness in 10 instances, mobilizing in 12 instances, influencing in 12 instances, evoking emotions in 9 instances, and motivating in 13 instances. Meanwhile, the functions of perlocutionary speech acts comprised persuading in 15 instances, inviting in 7 instances, influencing in 7 instances, inspiring in 8 instances, and touching emotions in 8 instances. These findings indicate that President Joko Widodo’s speech was used not only to convey information but also to shape the public’s ways of thinking, attitudes, emotions, and tendencies to act through persuasive, communicative, and contextual language. This study contributes to the development of pragmatic studies, particularly to the understanding of the use of perlocutionary speech acts in political communication through social media.